2019
DOI: 10.1016/j.ijom.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stem cells in maxillary sinus floor augmentation: systematic review and meta-analysis

Abstract: The aim of this review was to test the hypothesis of no difference in the efficacy of bone regeneration when using stem cells in maxillary sinus floor augmentation surgery in comparison to other grafts. Nine randomized clinical trials and one follow-up study involving human subjects were identified through a search of the PubMed/MEDLINE, Scopus, Cochrane, and Web of Science databases, supplemented by a hand search. No significant difference between groups was found for the implant survival rate, increase in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Os EA são aqueles considerados de origem inorgânica ou sintética, tais como a hidroxiapatita, beta-tricálcio fosfato e o vidrobioativo. Esses biomateriais, tanto de origem EX ou EA associados com fatores de crescimento, por exemplo, com a fibrina rica em plaquetas e leucócitos [14] ou células-tronco mesenquimais (do inglês, Mesenchymal Stem Cells, MSCs) [15,16], demonstram ser uma ferramenta interessante, posicionando-se assim com um agente adjuvante promissor visando a promoção das propriedades semelhantes aos de um enxerto, tais como, o fator de crescimento recombinante humano derivado de plaquetas [17] e o aspirado concentrado de medula óssea [18,19].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Os EA são aqueles considerados de origem inorgânica ou sintética, tais como a hidroxiapatita, beta-tricálcio fosfato e o vidrobioativo. Esses biomateriais, tanto de origem EX ou EA associados com fatores de crescimento, por exemplo, com a fibrina rica em plaquetas e leucócitos [14] ou células-tronco mesenquimais (do inglês, Mesenchymal Stem Cells, MSCs) [15,16], demonstram ser uma ferramenta interessante, posicionando-se assim com um agente adjuvante promissor visando a promoção das propriedades semelhantes aos de um enxerto, tais como, o fator de crescimento recombinante humano derivado de plaquetas [17] e o aspirado concentrado de medula óssea [18,19].…”
Section: Introductionunclassified
“…Estas características fazem com que seu uso possa ser uma ferramenta interessante para os procedimentos de enxertia, como em cirurgias de levantamento de seio maxilar. O uso de MSC associados aos enxertos para LSM tem sido foco de revisões sistemáticas [15,16] e a limitada evidência não suportam benefícios clínicos adicionais. Porém, não há até o momento, nenhuma revisão focando, especificamente, no BMAC.…”
Section: Introductionunclassified
“…Regarding thermosensitive hydrogel and stem cell transplant, it has been reported that chitosan/collagen‐bGP hydrogel is able to support growth of cells encapsulated in the hydrogels, and thus stem cell delivery 12 . To optimize functions of the transplanted cells, challenges are how to enhance viability and differentiation of the transplanted cells in a restricted environment of cell encapsulation and skeletal defects during an early stage of wound healing 13,14 . Quercetin (QT), a natural antioxidant, found in various fruits and tea leaves, can minimize cellular damage caused by free radicals, promote cell growth and osteoblastic differentiation and stimulate angiogenesis 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The most-reported graft material is xenograft mixed or not with autogenous bone. Use of stem cells has been also proposed, but according to a recent study, it seems not to significantly improve the implant survival rate, and/or the efficacy of bone regeneration following sinus lift procedure [15,16].…”
Section: Introductionmentioning
confidence: 99%